Disruption of Circadian Transcriptome in Lung by Acute Sleep Deprivation - Lu, Yuntao; Liu, Bing; Ma, Junjie; Yang, Shuo; Huang, Ju (Frontiers in Genetics, 2021)
Inadequate sleep prevails in modern society and it impairs the circadian transcriptome. However, to what extent acute sleep deprivation has impact on the circadian rhythms of peripheral tissues is not clear. Here, we show that in mouse lung, a 10-hour acute sleep deprivation can alter the circadian expression of approximately 3,000 genes. We found that circadian rhythm disappears in genes related to metabolism and signaling pathways regulating protein phosphorylation after acute sleep deprivation, while the core circadian regulators do not change much in rhythmicity. Importantly, the strong positive correlation between mean expression and amplitude (E-A correlation) of cycling genes has been validated in both control and sleep deprivation conditions, supporting the energetic cost optimization model of circadian gene expression. Thus, we reveal that acute sleep deprivation leads to a profound change in the circadian gene transcription that influences the biological functions in lung.